Penerapan Model Pembelajaran Modelling The Way Untuk Meningkatkan Keaktifan Siswa Kelas V SD Negeri 1001 Batang Bulu - Sutan Botung Hasibuan; Era Mutiah; Ali Sadikin Harahap (CV. Alim's Publishing, 2023)
This research aims to determine the application of the modeling the way learning model to increase student activity in Islamic Religious Education subjects regarding ablution and prayer in class V of SD Negeri 1001 Batang Bulu. The research used is classroom action research (PTK). Based on the research results, it can be concluded that: (1) Student activity before implementing the modeling the way learning model is still low. This can be seen from the results of observations that have been made. If we look at the level of activity, there are 5 students or 19% who have activity in the